Poverty considerations and income aspiration: a tale of two cities - Saade, Ahmed J.; Alexiou, Constantinos (Empirical Economics Letters, 2020)
The aim of this paper is to explore the role of poverty exposure in affecting income aspirations. In this direction, we collect samples from two relatively adjacent cities in Lebanon each with a different socioeconomic setting. The emerging evidence suggests that higher levels of education positively affects income aspirations, with education abroad being the most impactful across all estimated equations. The female population however consistently was found to have lower aspirations than their male counterparts across all estimated equations.
Keywords: Income Aspirations; Poverty; Education; Gender; Lebanon